Knowledge, attitude and practice of community-dwelling adults regarding advance care planning in Malaysia: a cross-sectional study. Issue 2 (14th February 2022) - Lim, Mun Kit; Lai, Pauline Siew Mei; Lim, Pei Shan; Wong, Pei Se; Othman, Sajaratulnisah; Mydin, Fadzilah Hanum Mohd
Abstract : Objectives: This study aimed to assess the knowledge, attitude and practice (KAP) among community-dwelling adults in Malaysia regarding advance care planning (ACP), and its associated factors. Design: This cross-sectional study was conducted from July–September 2018. Setting: This study was conducted at the University Malaya Medical Centre, Kuala Lumpur, Malaysia. Participants: We recruited community-dwelling adults (ambulatory care patients or their accompanying persons) who were ≥21 years old and able to understand English or Malay. A 1:10 systematic sampling procedure was used. Excluded were community-dwelling adults with intellectual disabilities or non-Malaysian accompanying persons. A trained researcher administered the validated English or Malay Advance Care Planning Questionnaire at baseline and 2 weeks later. Primary and secondary outcome measures: The primary outcome was the KAP regarding ACP. The secondary outcomes were factors associated with KAP. Results: A total of 385/393 community-dwelling adults agreed to participate (response rate 98%). Only 3.1% of the community-dwelling adults have heard about ACP and 85.7% of them felt that discussion on ACP was necessary after explanation of the term. The desire to maintain their decision-making ability when seriously ill (94.9%) and reducing family burden (91.6%) were the main motivating factors for ACP. In contrast, resorting to fate (86.5%) and perceived healthy condition (77.0%) were the main reasons against ACP. Overall, 84.4% would consider discussing ACP in the future. Community-dwelling adults who were employed were less likely to know about ACP (OR=0.167, 95% CI 0.050 to 0.559, p=0.004) whereas those with comorbidities were more likely to favour ACP (OR=2.460, 95% CI 1.161 to 5.213, p=0.019). No factor was found to be associated with the practice of ACP. Conclusions: Despite the lack of awareness regarding ACP, majority of community-dwelling adults in Malaysia had a positive attitude towards ACP and were willing to engage in a discussion regarding ACP after the term 'ACP' has been explained to them.